THE INFLUENCE OF DIGITAL LITERACY, LEARNING INDEPENDENCE, AND MOTIVATION ON ACADEMIC ACHIEVEMENT IN THE SUBJECT OF BUILDING CONSTRUCTION COST AND SCHEDULING PLANS AMONG GRADE XI DPIB STUDENTS AT SMK NEGERI 3 YOGYAKARTA - Anggie Fadhlia Ash Shaf; P Priyanto (International Journal of Cultural and Social Science, 2025)
This study investigates the influence of digital literacy, learning independence, and learning motivation on student achievement in the subject of cost planning and scheduling among Grade XI students of the Building Modeling and Information Design (DPIB) program at SMK Negeri 3 Yogyakarta. Using a quantitative ex post facto design, the study involved 99 students selected from a population of 131 through proportional cluster random sampling. Data on the independent variables were collected using validated questionnaires, while achievement scores were obtained from teacher assessments. The results of multiple regression analysis show that digital literacy, learning independence, and learning motivation each have a significant positive effect on learning achievement, both individually and simultaneously. These findings emphasize the need for vocational education to enhance students’ digital skills, promote self-directed learning, and foster motivation. The study offers practical insights for educators and curriculum planners and suggests further research to explore additional psychological or contextual factors affecting learning outcomes.